Inga uruguensis response to lead: effects on growth and nitrogenous compounds - Frachia, Caroline de Lima [UNESP]; da Silva, Victor Navarro [UNESP]; de Paiva, Wesller da Silva [UNESP]; Barbosa, Isis Caroline Ferreira [UNESP]; da Silva, Mariana Bocchi [UNESP]; Souza, Lucas Anjos; Justino, Gilberto Costa; de Camargos, Liliane Santos [UNESP] (FapUNIFESP (SciELO), 2022)
Lead (Pb) is a heavy metal considered one of the major soil pollutants. Phytoremediation is a sustainable and economically viable biological method for reducing Pb content in the environment. Inga uruguensis is a tree legume species that has characteristics favorable to phytoremediation, such as rapid growth and high biomass production. The objective of this work was an initial evaluation of tolerance and phytoremediation potential of I. uruguensis to Pb. The experiment was carried out in a greenhouse. In addition to the control, soil contamination was carried out with the following Pb doses: 100, 200, 300, 400, and 500 mg.dm3 with 5 repetitions in each treatment, totaling 30 vases. We assessed growth, number and mass of nodules, chlorophyll content, ureids, amino acid, protein and soluble carbohydrates in leaves, roots and nodules, tolerance index, dry matter, and tissues Pb content of I. uruguensis. The data were analyzed by the Tukey test using R and SISVAR software. There was no negative effect of Pb in soil on I. uruguensis growth, the symbiotic relationship with rhizobia was kept, even at high Pb content and the tolerance index was not lower than 0.69. Inga uruguensis has initial tolerance and potential to be used as phytoremediation in soils contaminated by Pb.
Keywords: heavy metal; phytoremediation; phytostabilization; tree legume